THE STUDENTS’ ABILITY TO LEARN ENGLISH AT THE TENTH GRADE OF SMAIT AR-RAHMAH MAKASSAR - Nur Khamisah; Andi Tenri Ampa; Junaid (Journal of Language Testing and Assessment, 2022)
The objective of the research is to find students’ ability to Learn English at the tenth grade of SMAIT Ar-Rahmah Makassar. The research method is descriptive design with a quantitative approach. The population for this study is tenth-grade students at SMAIT Ar-Rahmah Makassar. The sample of this research was tenth grade, which contains 40 students. The research used Report text as the instrument of the research. The findings of the research shows that that the ability of in reading comprehension the students is quite good because the result categorize as fairly good. the level of students’ ability to learn English in Critical Reading is average. There are 74% (Fairly Good) the ability in terms of comprehension indicator. The ability of the students to Analyze the text in critical reading 68% (Fairly Good). The ability of the students in terms of Synthesis 71% (Fairly Good). The ability of the students to evaluate the report text 67% categorized as Fairly good. The highest ability of the students in terms critical reading to learn English is indicator of comprehension